Optimalisasi Limbah Bekas Solar dengan Filterasi Bisa Digunakan Kembali 85 % Dari Jumlah Solar Yang di Filterasi - Aris Aryanto; Tedy Mandela; Adhyaksa Prasidya; Hasbu Arrosyid; Ragil Kusuma Jati (CV. Green Publisher Indonesia, 2026)
Background: in the mining industry, especially coal, is a vital part of the global economy, providing vital energy resources for the world. However, to ensure the continuity and profitability of a mining business, managing operational costs is crucial, especially as fuel costs account for 30-35% of operating costs. Purpose: this research aims to reduce and optimize waste, used diesel fuel from fuel management activities can be reused 85% so that the goals, targets and K3PLM programs of PT Putra Perkasa Abadi Job site Bukit Asam Div Fuel discrepancy, cost filtration and cleanlines fuel are achieved according to the target. Methods:. this research method that involves sampling and data collection, thus filtering techniques are used with visualization of the quality and quantity of solar energy, allowing the collected data to be analyzed descriptively. It does not seek relationships or influences between variables, but focuses solely on describing facts. It also presents real data from the field. Results: the results of the study show that the real data on the results of used diesel waste collected and then filtered during September to November 2025 can be optimized and reused 95% of the September diesel, 91% of October and 96% of November from the amount of used diesel waste Conclusion: the DS100-10 filtration used to optimize diesel waste can produce diesel with quantity and quality based on clear diesel visuals and ISO 4406 cleanlines below the standard and can be reused above 85% of diesel waste and can reduce diesel costs.